Factors associated with upper leg muscle strength in knee osteoarthritis: A scoping review - Arjan H de Zwart; Joost Dekker; Willem Lems; Leo D. Roorda; Martin van der Esch; Marike van der Leeden (Medical Journals Sweden, 2017)
Objective: Muscle weakness is common and strongly related to clinical outcome in patients with knee or hip osteoarthritis. To date, there is no clear overview of the information on factors associated with muscle strength in knee and hip osteoarthritis. The aim of this paper is to provide an overview of current knowledge on factors associated with upper leg muscle strength in this population. Design: The framework of a scoping review was chosen. MEDLINE database was searched systematically up to 22 April 2017. Studies that described a relationship between a factor and muscle strength in knee or hip osteoarthritis were included. Results: A total of 65 studies met the inclusion criteria. In studies of knee osteoarthritis, 4 factors were consistently found to be associated with lower muscle strength. Due to the low number of studies on hip osteoarthritis no conclusions could be drawn on associations. Conclusion: Lower muscle quality, physical inactivity, more severe joint degeneration, and higher pain are reported to be associated with lower strength in the upper leg muscles in knee osteoarthritis. Future research into knee osteoarthritis should focus on other potential determinants of muscle strength, such as muscle quantity, muscle activation, nutrition and vitamins, and inflammation. In hip osteoarthritis, more research is needed into all potential determinants.